2010
DOI: 10.3342/ceo.2010.3.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nebulized Bovine Surfactant for Experimental Otitis Media with Effusion

Abstract: ObjectivesIn this study, we evaluated the efficacy of nebulized bovine pulmonary surfactant on experimentally induced otitis media with effusion (OME) in guinea pigs.MethodsTwenty guinea pigs were divided into three groups. Four untreated animals served as normal controls. Experimental OME was established in both ears of the remaining 16 animals by a transbullar injection of 10 µL of Pseudomonas aeruginosa lipopolysaccharide in saline. Thereafter, the guinea pigs received nebulized phosphate buffered saline (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…On the other hand, more animals might be needed for statistical significance of goblet cell count in the cartilaginous ET. Some recent studies using light microscopy or scanning electron microscopy found that transnasal PS reduced the thickness of the subepithelial layer, edematous mucosa, and glandular hyperplasia in the middle ear epithelium …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, more animals might be needed for statistical significance of goblet cell count in the cartilaginous ET. Some recent studies using light microscopy or scanning electron microscopy found that transnasal PS reduced the thickness of the subepithelial layer, edematous mucosa, and glandular hyperplasia in the middle ear epithelium …”
Section: Discussionmentioning
confidence: 99%
“…Based on this background, the intranasal instillation or local nebulization of surfactants has been tested in a number of animal models of experimental otitis media. The data consistently showed that local surfactant therapy has several benefits as it may (1) protect mucosa and reduce secretions, (2) favor tubes’ opening and secretions sliding, and (3) improve local histology and clinical course 66‐76 . These studies used animal surfactant preparations commonly used for respiratory indications 18 and have also been studied in combination with other treatments, such as local steroids, without significant differences 71,72 .…”
Section: Possible Extrapulmonary Surfactant Indicationsmentioning
confidence: 93%
“…The data consistently showed that local surfactant therapy has several benefits as it may (1) protect mucosa and reduce secretions, (2) favor tubes' opening and secretions sliding, and (3) improve local histology and clinical course. [66][67][68][69][70][71][72][73][74][75][76] These studies used animal surfactant preparations commonly used for respiratory indications 18 and have also been studied in combination with other treatments, such as local steroids, without significant differences. 71,72 Conversely, the addition of phenylephrine had a negative effect and was also able to abolish the effect of surfactant.…”
Section: Otitis Mediamentioning
confidence: 99%
“…Replacement surfactants consist of lipid extract preparations obtained from animal bronchoalveolar fluids, containing phospholipids, mainly DPPC, and the hydrophobic proteins SP-B and SP-C ( 26 ). Interestingly, replacement surfactants also improve recovery of animal models of otitis media ( 27 , 28 ). Lipoprotein structures similar to lung surfactant seems to be present in other mucosal surfaces exposed to the external environment, suggesting the importance of these lipoprotein structures.…”
Section: Introductionmentioning
confidence: 99%